Gender Representation at Conferences, Executive Boards, and Program Committees in Otolaryngology. (16th July 2020) - Barinsky, Gregory L.; Daoud, Deborah; Tan, Didem; Cerasiello, Samantha Y.; Silva, Nicole A.; Grube, Jordon G.; Baredes, Soly; Gray, Stacey T.; Eloy, Jean Anderson
Abstract : Objective: Women represent approximately 28.0% of academic otolaryngologists. Previous studies have shown that women in academic medicine, including surgical subspecialties, have disparate career advancement opportunities and grant funding compared to male counterparts. Representation at major academic meetings is an important career advancement opportunity. In this study, we assess the representation of women at otolaryngology conferences. Study Design: Cross‐sectional analysis of otolaryngology conference programs. Methods: All publicly available scientific programs from The American Academy of Otolaryngology–Head and Neck Surgery Foundation Annual Meeting (AAO‐HNSF), the Triological Society Annual Combined Sections Meeting (TS), and the Triological Society Annual Meeting at Combined Otolaryngology Spring Meetings (TS‐COSM) were obtained and analyzed. Name and gender were collected, along with the type of role: speaker, panelist, oral session moderator, and other leadership positions. Yearly trends were analyzed and compared between the conferences and in aggregate. Results: AAO‐HNSF had available scientific programs from 2012–2017, while TS and TS‐COSM had programs available from 2003–2018. Across all conferences and years, 16.9% of recorded opportunities were occupied by women, with an upward trend from 2005 to 2018. Program committees had the highest proportion of women (21.4%) and presidential citation and guest of honor recipients had the lowest (9.1%). Of all panels, 87.5% did not have any women panelists in 2003, but by 2018 only 24.0% panels were male‐only. There was marked repetition among women occupying roles, with only 423 unique women occupying a total of 1, 733 filled spots. Conclusion: Measured representation of women in academic otolaryngology conferences has improved from 2003–2018. Despite this improvement, gender disparity still exists. Level of Evidence: 5 Laryngoscope, 131:E373–E379, 2021